Assessing the Toxicity of Leachates From Weathered Plastics on Photosynthetic Marine Bacteria Prochlorococcus - Sarker, Indrani; Moore, Lisa R.; Paulsen, Ian T.; Tetu, Sasha G. (Frontiers in Marine Science, 2020)
Marine plastic pollution is a well-recognized, global problem. Research addressing plastic pollution has largely focused on investigating impacts on macroorganisms, with few studies investigating effects on marine microbes. We previously showed that marine Prochlorococcus, which are important contributors to oceanic primary production, suffer declines in growth and photosynthetic activity following exposure to leachates from new plastic bags (HDPE) and plastic matting (PVC). However, as such plastics reside in the environment they will be subject to weathering processes, so it is also important to consider how these may alter the composition and amounts of substances available to leach. Here we report on how plastic leachate toxicity is affected by environmental weathering (17- and 112-days in estuarine water) of these common plastic materials. We found that while toxicity was reduced by weathering, materials weathered for up to 112-days continued to leach substances that negatively affected Prochlorococcus growth, photophysiology and membrane integrity. Weathered plastics were found to continue to leach zinc, even after up to 112-days in the environment. The two Prochlorococcus strains tested, NATL2A and MIT9312, showed differences in the sensitivity and timing of their responses, indicating that exposure to leachate from weathered plastics may affect even closely related strains to different degrees. As many marine regions inhabited by Prochlorococcus are likely to be subject to continued accumulation of plastic pollution, our findings highlight the potential for ongoing impacts on these important primary producers.